USER PERCEPTION STUDY OF RIVER TRANSPORT MODE (CASE STUDY: MODE OF RIVER TRANSPORTATION IN KUANTAN QUIET VILLAGE - MEDAN CITY VILLAGE, INDRAGIRI HULU REGENCY) - Sahriyal, Sahriyal (RADJA PUBLIKA, 2022)
The historical development of Riau Province is inseparable from the waters, one of which is a river. The river is the only mode of transportation used. Indragiri Hulu Regency is one of 9 regencies/cities in Riau Province which is crossed by a river with a length of 500 km with a depth of 6-8 meters, namely the Indragiri River. River mode of transportation is an alternative mode currently connecting areas separated by rivers. Kuantan Tenang Village and Medan City Village, Indragiri River is the barrier between the two villages. The river mode of transportation is still the transportation used by these two villages as a liaison to get to the village. The purpose of this study is to describe people's perceptions as users of river transportation modes with case studies of river transportation modes in Kuantan Tenang Village and Medan City Village, Indragiri Hulu Regency. The method used in this study uses field observations through a questionnaire questionnaire given to users of river transportation modes in the case study location. The number of respondents is 50 respondents based on 9 characteristics. User perceptions of river transportation modes linking Kuantan Tenang Village, Rakit Kulim District with City Village Medan, Kelayang District, Indragiri Hulu Regency based on a study of perceptions of the level of service quality where the results of the analysis were obtained with a mean number of 4.33, with a good category, perceptions of tariff analysis where the results of the analysis were obtained with a mean number of 4.67, with a very good category, and perceptions on Mode Satisfaction where the results of the analysis are obtained with a mean number of 4.25 with a Good Category so that the results of the study of user perceptions of river transportation modes in Kuantan Tenang Village - Medan City Village with a mean number of 4.42 in the Good category are needed. The link to river transportation, especially those along the Indragiri river, is the construction of completeness facilities, namely the pier.